Evidence-Based Urology: How Does a Randomized Clinical Trial Achieve Its Designed Goals? - Sadeghi Bazargani, Homayoun; Hajebrahimi, Sakineh (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> Purpose: To discuss the methodological considerations of a standard and applicable randomized clinical trial (RCT). Materials and Methods: Using a predefined strategy, we conducted systematic computerized search of the MEDLINE (1966 to 2011) and EMBASE (1980 to 2011) databases to identify all English language educational articles discussing the RCT methodological aspects. Full text versions of identified studies were reviewed in blinded fashion for key methodological and statistical characteristics. Results: Randomized clinical trials in surgery are the highest level of the primary research evidence in evidence-based medicine. There is increasing demand for implementation of RCTs in urological daily practice. Conclusion: Randomized clinical trials’ report should be absolutely clear, simple, and easy to understand with well-defined internal and external validity. Efforts should be made to design high quality RCTs in urology. There are substantial needs for urologists to their knowledge about RCT.